PEMANFAATAN APLIKASI PENGOLAH PRESENTASI DALAM MENDUKUNG PEMBELAJARAN DI SMA TARSISIUS 1 JAKARTA - Geasela, Yemima Monica; Lee, Francka Sakti; Bernanda, Devi Yurisca; Agustina, Agustina; Andrian, Andrian (Jurnal Pengabdian dan Kewirausahaan, 2021)
ABSTRACT                The Community Service Program organized by the Information System of Bunda Mulia University with the title "Utilizing Presentation Processing Applications in Supporting Learning at SMA Tarsisius 1 Jakarta", the main activity was carried out, namely providing training related to learning support application systems in the form of presentation processing applications. This activity was carried out online (virtual) with the help of google meet media due to the pandemic situation, namely COVID-19, which made this activity unable to be carried out offline (onsite). The main target of this activity is aimed at students who attend SMA Tarsisius 1 Jakarta. This activity aims to help increase the knowledge of the participants regarding the functional features available in the presentation processing application so that the participants can use the application by maximizing all the features of the existing functions. The method used in this activity is to apply a demonstrative teaching model and participants can see firsthand how to use the existing features so that it is easier to absorb. At the end of the activity, a questionnaire was distributed as feedback from the students of SMA Tarsisius 1 Jakarta regarding the training that had been given. The conclusion of this activity shows that the training on the use of this presentation processing application is going well with the results of feedback stating that 84.47% of participants stated that the material and the implementation of the activities were clearly easy to understand, and 83.68% of participants stated that the instructor delivered the material clearly and helped the participants understand the activity material well.